Portal venous gas accompanied by gallbladder torsion: a case report. Issue 10 (31st October 2022) - Tohma, Takayuki; Kobe, Yoshiro; Yoshida, Mitsuhiko; Ushio, Masaya
Abstract: Portal venous gas (PVG) generally suggests critically ill conditions such as severe bowel ischemia. We herein report a rare case of gallbladder torsion with PVG. An 88-year-old woman complained of right hypogastric pain. Ultrasonography (US) showed diffuse wall thickening of her gallbladder and mobile echogenic foci moving inside the portal venous branches. Computed tomography showed a thickened wall of the gallbladder with poor enhancement and tiny pockets of air in the portal venous branches (segments 4 and 5). There was no evidence of other visceral ischemia. She was diagnosed with necrotic cholecystitis and immediately underwent an emergency operation. We found a gangrenous gallbladder with 180° clockwise rotation along the longitudinal axis and performed cholecystectomy. We confirmed the disappearance of PVG with US after the operation. Her postoperative course was uneventful. Gallbladder diseases can produce PVG, and US might be a useful diagnostic modality to evaluate changes in PVG.